The Influence of Maternal Factors on Caesarean Section at North Borneo Regional Hospital, Kalimantan, Indonesia - Padlillah, Rahmi; Yulianti, Ika; Linda, Nur (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2025)
Background: In this modern era, caesarean section (C-section) is sometimes an alternative choice for the desired childbirth. However, it should be understood that Caesarean section is a surgical procedure that must be performed based on medical indications and has risks. Knowing what factors can influence the selection of C-section procedures is important so that the SC is properly carried out on an emergency indication. This study aimed to analyze the factors that affect the delivery of caesarean section at the Tarakan General Hospital, Kalimantan, Indonesia. Subjects and Method: A cross-sectional study was conducted at Tarakan General Hospital, North Kalimantan, Indonesia, in April 2024. The sample size was 748 post natal women. The dependent variable was type of birth delivery. The independent variables were cephalopelvic disproportion, preeclampsia, prolonged labor, premature rupture of membranes, maternal age, and parity. Data were obtained from medical records and analyzed using a multiple logistic regression. Results: Premature rupture of membranes (aOR= 7.7; 95% CI= 6.99 to 8.02; p= 0.001) and prolonged labor (aOR= 1.9; 95% CI= 1.21 to 3.6; p= 0.029) increased the likelihood of cesarean section. Conclusion: Premature rupture of membranes and prolonged labor increase the likelihood of cesarean section.